How Three Different Translators of The Holy Qur’an Render Anthroponyms from Arabic into English - Mahmoud Afrouz (Names, 2021)
The present paper examines anthroponyms in the Holy Qur'an in three different English translations to shed light on how procedures used by translators can help target-language (TL) readers understand the implied meaning of anthroponyms. In order to conduct the research, the anthroponyms in the Holy Qur'an were isolated and English equivalents were identified. Then Vermes’s (2003) model was applied to the collected data to find answers to the following research questions: (1) What strategies are used most frequently by the translators examined to render the Qur’anic anthroponyms into the target-language (TL)?; (2)  How consistent are the translators in using particular strategies when translating the anthroponyms?; (3) Does the type of translator affect their choice of translation strategy?; (4) Does the model suggested by Vermes (2003) cover all of the strategies employed by the three translators?; and (5) Which procedures are source-language-oriented, TL-oriented, or deep-reader oriented? Overall, the findings indicated that the procedures most frequently used by the translators were “substitution” and “transference.” It was found that the native speaker of neither Arabic nor English foreignized 96.80% of the Qur’anic anthroponyms by using “transference,” while the native translators of either the target-language or the source-language domesticated 71.00% of the anthroponyms by using “substitution.” “Substitution” was used when an exact Biblical equivalent for the Qur’anic anthroponym existed. Otherwise, “transference” was used along with notes to transport the meaning and form while remaining faithful to the intended meaning of the sacred text.